Skeptical Look at the Clinical Implication of Metabolic Syndrome in Childhood Obesity - Malgorzata Wasniewska; Giorgia Pepe; Tommaso Aversa; Simonetta Bellone; Luisa de Sanctis; Procolo Di Bonito; Maria Felicia Faienza; Nicola Improda; Maria Rosaria Licenziati; Claudio Maffeis; Alice Maguolo; Giuseppina Patti; et al. (Children, 2023)
Metabolic syndrome (MetS) is defined by a cluster of several cardio-metabolic risk factors, specifically visceral obesity, hypertension, dyslipidemia, and impaired glucose metabolism, which together increase risks of developing future cardiovascular disease (CVD) and type 2 diabetes mellitus (T2D). This article is a narrative review of the literature and a summary of the main observations, conclusions, and perspectives raised in the literature and the study projects of the Working Group of Childhood Obesity (WGChO) of the Italian Society of Paediatric Endocrinology and Diabetology (ISPED) on MetS in childhood obesity. Although there is an agreement on the distinctive features of MetS, no international diagnostic criteria in a pediatric population exist. Moreover, to date, the prevalence of MetS in childhood is not certain and thus the true value of diagnosis of MetS in youth as well as its clinical implications, is unclear. The aim of this narrative review is to summarize the pathogenesis and current role of MetS in children and adolescents with particular reference to applicability in clinical practice in childhood obesity.